Genetic diversity analysis of Iris germanica cultivars based on ISSR and SRAP molecular markers - Bo, Wei; Wang, Song; Xing, Guoming; Wang, Yuguo (Frontiers in Plant Science, 2025)
IntroductionIris germanica L. (1753), commonly known as bearded iris, is a popular ornamental plant species appreciated for its beautiful and diverse flower colors and forms. Despite its aesthetic appeal, there is limited knowledge about the genetic diversity and relationships among Iris germanica cultivars.MethodsTo address this, in this study, we investigated the genetic diversity and molecular clustering of Iris germanica cultivars through ISSR and SRAP molecular markers.ResultsOur analysis identified that ISSR analysis revealed a high level of genetic diversity among Iris germanica cultivars. The 9 ISSR primers generated 72 amplified bands, of which 66 were polymorphic, yielding a polymorphism percentage of 89.86%. Similarly, SRAP analysis demonstrated substantial intraspecific genetic diversity. 12 SRAP primer pairs produced 693 amplified bands, with 669 exhibiting polymorphisms, corresponding to a polymorphism rate of 96.54%. Genetic similarity coefficients ranged from 0.513 to 0.868 for ISSR and 0.595 to 0.801 for SRAP markers, highlighting variations and relationships among Iris germanica accessions. ISSR Molecular marker cluster analysis categorized divides Iris germanica cultivars with similar morphological characteristics into distinct groups to a certain extent based on genetic similarity coefficients, and SRAP marker could also make the same species from different regions first cluster into one group based on classifying the similar phenotypic Iris germanica varieties, indicating that the SRAP marker used to analyze the genetic diversity of Iris germanica cultivars were more accurate than the ISSR marker. Combining both ISSR and SRAP markers not only effectively distinguished between dwarf and tall species of Iris germanica, but also separately isolated two Iris germanica species from Shanxi province. It had also been found that Iris germanica Antique Red, Iris germanica Indian leader were clustered into one group and Iris germanica Bloodstone and Cherry Garden were gathered together in three kinds of clustering methods, indicating that these varieties had very close relationship.DiscussionOverall, this study provides valuable insights into the genetic diversity and relationships within Iris species, offering important implications for breeding and conservation efforts.